“Conocimientos y actitudes sobre el SIDA entre estudiantes de colegios secundarios del distrito de Tarapoto – 1995” - Díaz Espinoza, Flor de María (1997)
This paper is a descriptive study with prospective collection of data retrieved from the students of the last year of secondary schools in the district educaci6n. Tarapoto. For execution was used descriptive correlational design, using the information on-site based on surveys, took a sample of 794 students of which 380 were males and 414 women. Students received sex education by 64% and 71% in the home more school. There was more knowledge about talks of methods contraceptive in the home as in the school, the method contraceptive more used was the condom with a 85%. The source of further information received on the acquired immunodeficiency syndrome was television. AIDS and gonorrhea are sexually transmitted diseases best known occupying the first places. 7. the attitude that have students toward the co ~ gifts is 90%. In terms of the awareness of the transmission of the virus...